Malay aesthetic concept through malay woodcarving motifs in visual artworks / Nuratikah Abu Hassan, Ponirin Amin and Suhaimi Tohid - Abu Hassan, Nuratikah; Amin, Ponirin; Tohid, Suhaimi (2016)
Woodcarving is a cottage industry for the Malays in ancient times and it is one of the tangible heritages that should be preserving and sustained. Unfortunately, it is not widespread and only covers the states on the East Coast as Kelantan, Terengganu and Pahang. Traditional Malay woodcarving depicts the Malay concept of beauty, which governs seven basic principles, like spiritualism or mysticism, unity, symbolism, refinement, and flexibility. Furthermore, this study is to identify the Malay traditional woodcarving motifs in visual artworks based on interpretations of Malay aesthetic principles and elements in order to proven that the motifs is represent the Malay aesthetic concept. The various selected samples of artworks has been identify and analysed used a theory of Malay beauty concept by Zakaria Ali (1989). Qualitative methods are applied in this study and it based on the process of gather the data analysis form the literature within Malay aesthetic context and interlinking it to the visual analysis artwork. Indeed, the outcome of this study the motifs in the visual artworks which have represent a Malay aesthetic and it will sustain the uniqueness of Malay art in Malaysia for the next generations to appreciate it.